Encyclopedia of knot theory - Adams, Colin (Colin Conrad), 1956- (Boca Raton, FL : A Chapman & Hall Book, CRC Press, 2021)
"Knot theory has proven to be a fascinating area of mathematical research, dating back about 150 years. Encyclopedia of Knot Theory provides short, interconnected articles on a variety of active areas in knot theory, and includes beautiful pictures, deep mathematical connections, and critical applications. Many of the articles in this book are accessible to undergraduates who are working on research or taking an advanced undergraduate course in knot theory. More advanced articles will be useful to graduate students working on a related thesis topic, to researchers in another area of topology who are interested in current results in knot theory, and to scientists who study the topology and geometry of biopolymers. Features Provides material which is useful and accessible to undergraduates, post-graduates, and full-time researchers Topics discussed provide an excellent catalyst for students to explore meaningful research and gain confidence and commitment to pursuing advanced degrees Edited and contributed to by top researchers in the field of Knot Theory"--
OCLC-licensed vendor bibliographic record.
Keywords: Knot theory -- Encyclopedias; MATHEMATICS / General; MATHEMATICS / Geometry / General; MATHEMATICS / Recreations & Games